Advanced technical drawing - Classroom Video (New South Wales : Classroom Video, 1988)
Stuart Arden demonstrates and discusses basic drawing systems, reference envelopes, circles in paraline and perspective, the process of preparing drawings that will convey technical information, traditional perspective, measuring point perspective, and drawing complex objects
VCD format
Keywords: Engineering graphics; Engineering drawings; Mechanical drawings